Cold induces brain region-selective cell activity-dependent lipid metabolism - Hyeonyoung Min; Yale Y Yang; Yunlei Yang (eLife)
It has been well documented that cold is an enhancer of lipid metabolism in peripheral tissues, yet its effect on central nervous system lipid dynamics is underexplored. It is well recognized that cold acclimations enhance adipocyte functions, including white adipose tissue lipid lipolysis and beiging, and brown adipose tissue thermogenesis in mammals. However, it remains unclear whether and how lipid metabolism in the brain is also under the control of ambient temperature. Here, we show that cold exposure predominantly increases the expressions of the lipid lipolysis genes and proteins within the paraventricular nucleus of the hypothalamus (PVH) in male mice. Mechanistically, by using innovatively combined brain-region selective pharmacology and in vivo time-lapse photometry monitoring of lipid metabolism, we find that cold activates cells within the PVH and pharmacological inactivation of cells blunts cold-induced effects on lipid peroxidation, accumulation of lipid droplets, and lipid lipolysis in the PVH. Together, these findings suggest that PVH lipid metabolism is cold sensitive and integral to cold-induced broader regulatory responses.